Candida albicans Biofilm growth and Dispersal: Contributions to Pathogenesis - Wall, Gina (Curr Opin Microbiol, 2019)
The fungal species Candida albicans is most frequently associated with biofilm formation in immune-and medically-compromised patients, and it is now firmly established that biofilm formation represents a major virulence factor during candidiasis. A growing body of evidence has demonstrated that C. albicans biofilm development is a highly regulated and coordinated process, where adhesive interactions, morphogenetic conversions and consortial behavior, play significant roles. Cells within the biofilms are protected from environmental stresses including host immune defenses and antifungal treatment, which carries important clinical consequences for the treatment of biofilm-associated infections. Dispersal of cells from biofilms represents one of the hallmarks of the biofilm life-style, and in the case of C. albicans dispersed cells are responsible for candidemia and dissemination leading to the establishment of invasive disease.